Secure data transmission and authentication scheme using advanced blockchain cryptography approach for protecting financial assets in decentralized third party intranet communication - Iliyas, S. Mohammed; M. Mohamed Surputheen (International Journal of Computational and Experimental Science and Engineering, 2025)
As the digital landscape advances, the need for robust security mechanisms in the transmission and authentication of data, particularly in financial sectors, becomes increasingly critical. This progressive data transmission and authentication scheme leveraging advanced blockchain cryptography for the protection of financial assets across decentralized third-party intranet communications. Traditional security methods, widely employed in contemporary systems, have exhibited numerous vulnerabilities leading to security breaches, token mismanagement, and susceptibility to packet injections, culminating in compromised security keys. To resolve this. This paper presents an innovative approach leveraging advanced blockchain cryptography to protect financial assets during inter-party communication. The proposed method begins with the generation of a data block based on a Hash Index Policy (HIP) that systematically enhances data integrity. Then create of Proof Of Key Stack (PoKS) for chain link shuffle status and Private keys are generated with role of access rights. Finally, the Peer End Master Node Authentication (PEMNA) verifies the key authenticity to handover the data to ensure the safety to the access right person. The final authentication process is governed by a peer-end master node, which rigorously verifies key authenticity prior to data handover, ensuring that only authorized individuals can access sensitive information. The proposed system demonstrates superior security performance metrics compared to conventional methods, evidenced by enhancements in cryptographic policy compliance, authentication validity, and key verification processes. The proposed system proves higher security performance as well in Crypto-policy enrich standard, proof of authentication, key validation, verification and higher secured true positives rates to allow permissions to improve the security compared to the tradition methods.